Efectivity Between Dry Needling And Laser Combinated With Core Stability Exercise For Pain Reduction On Complaints Of Myogenic Low Back Pain - Saifudin Zuhri; Marti Rustanti (Jurnal Keterapian Fisik, 2022)
Background: The majority of people who experience myogenic low back pain (LBP) do so while going about their normal lives. Compared to other physical therapy technology applications, the combination of laser and dry needling with core stability exercises for LBP myogenic pain has not been utilized as frequently in clinical practice. Methods: Purposive sampling is used to select subjects. Subjects were those who fit the criteria of the study and reported experiencing myogenic LBP. The number of subjects in group I was 35 subjects and group II was 34 subjects. Experimental study with two groups participating in pre and post-testing. Phase I of the research was conducted in 2021 at the Sunafa physiotherapy practice, Colomadu, and Karanganyar. Phase II of the research was conducted there in 2022. After discovering that the research data was not normally distributed, a nonparametric test was conducted. Results: The combination of core stability exercises and dry needling reduced myogenic LBP complaints (p = 0.000), using laser therapy along with core stability exercises significantly reduced the number of complaints of myogenic LBP (p = 0.000). Dry needle and core stability exercise, as well as laser and core stability exercise, both reduced pain in the same way as myogenic LBP complaints (p = 0.242). Conclusion: Both laser therapy and dry needling combined with core stability exercises are useful in easing myogenic LBP complaints.